Deconstructing the Female Quest in Nigerian Cartoons - Oladesu, Johnson Olarinde (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
In an attempt to present an issue of topical interest, an author of a text or imagery is expected to depict two voices. The first voice, could be that is the antagonist that is given to negativity and vice, while, the other voice must be given to correction that is aimed ameliorating a dwindling situation. The cartoonist’s work under study presents a biased view of the female identity such that there is a male-centred negative perception of the female character used in driving the story he has written. This study challenges this stereotyping at a time that several scholars continue to call for a balanced presentation of the female identity. The female identity as presented in the works of other mostly male cartoonists is weighted against the works Nd’Usoro whose work is the subject of discussion. The work of a female cartoonist that has used a female character to advance a positive female stereotype is presented to set the tone for the article. It also brings to bare the works of authors of African literature and the pertinent issues raised in favour of the female gender as a textual parallel to the thrust of the article.